Developmental polymorphism and the Brooks-Dyar law (2018)
Many protocols for research in insect biology and ecology require accurate determination of larval instar. The Brooks-Dyar Law (1886, 1890) states that the measurement of sclerotized structures follows a predictable regular geometric progression that can be used to determine accurately both larval instar of single larvae and the number of instars before pupation in a population. The Brooks-Dyar Law has been used extensively in studies of a number of holometabolous and hemimetabolous orders. Although the Brooks-Dyar’s Law describes the variation in size among insect larvae as a function of development, the mathematical formula of the law has only been defined empirically, without any insights on the biological meaning of parameters (but see Hutchinson et al. [1997]). Moreover, the current definition assumes that insects go through a fixed number of instars before pupation, which is not always the case for many insect orders (Esperk et al. 2007).